Multidisciplinary decision‐making regarding chemotherapy for lung cancer patients—An age‐based comparison. (21st September 2017) - Schulkes, K.J.G.; Hamaker, M.E.; Lammers, J.‐W.J.; van Rens, M.T.M.; Geerts, M.; van Elden, L.J.R.
Abstract : Optimising decision‐making in elderly patients is becoming increasingly urgent. We analysed treatment decisions and course of therapy for patients with lung cancer in different age categories: <65, 65–75, and 75 years and older. About 349 patients with lung cancer (median age 67.8 years), discussed at the multidisciplinary team meeting in the Diakonessenhuis Utrecht, the Netherlands, were reviewed. Multidisciplinary decision‐making and subsequent clinical course were extracted from medical files. We found that 39% of eligible patients older than 75 years of age started treatment with chemotherapy compared to 80% of the younger patients (<65 and 65–75). When patients did receive chemotherapy, primary and secondary treatment adaptations were effectuated in 58%: for patients aged <65 in 49%, for patients aged 65–75 and >75 years in 66%. For 44% of all patients treated with chemotherapy, unplanned hospital admissions were required: in 42% for the patients <65, in 52% for those aged 65–75 and in 27% for >75 years. The decision‐making process and course of treatment for lung cancer vary per age category. In particular, patients between 65 and 75 years of age might be more frail than initially thought. Age and frailty are important characteristics that need more attention.